Filling an Information Gap in Preschool MTSS and RTI Decision Making. (April 2019) - Greenwood, Charles R.; Carta, Judith J.; Schnitz, Alana G.; Irvin, Dwight W.; Jia, Fan; Atwater, Jane
A tenet of multitiered systems of support and response to intervention (MTSS-RTI) is that lack of response to instructional intervention is explained by classroom experiences and behaviors given opportunities to learn. We investigated the potential of filling this information gap in MTSS-RTI decision making using ecobehavioral observation to inform steps that could be taken for children not responding to preschool literacy instruction. Data analyses indicated that (a) teachers implemented a uniform pattern of daily activities providing children with infrequent opportunity to learn literacy, (b) the proportion of children's co-occurring academic engagement also was low but varied widely depending on the activity and teacher's literacy focus, and (c) children's personal risk characteristics moderated the strength of relationships. Novel was the finding that in some activities and teacher behaviors, teachers appeared to be differentiating instruction benefiting children with individualized education programs and dual-language-learner risk. Implications are discussed.